Post‐Traumatic Stress Disorder: Ethical and Legal Relevance to the Criminal Justice System. Issue 2 (June 2014) - Soltis, Kathryn; Acierno, Ron; Gros, Daniel F.; Yoder, Matthew; Tuerk, Peter W.
<x xml:space="preserve">Abstract</x> Post‐Traumatic Stress Disorder is a major public health concern in both civilian and military populations, across race, age, gender, and socio‐economic status. While PTSD has been around for centuries by some name or another, its definition and description also continue to evolve. Within the last few years, the American Psychological Association has published the 5th edition of the Diagnostic and Statistical Manual of Mental Disorders, which includes some major changes in the diagnostic criteria for PTSD. Recent data on epidemiology, etiological theories, and empirically supported methods of treatment, as well as implications for legal processes and criminal justice system personnel, are discussed.